Degree of conversion of polymer-matrix composite assessed by FTIR analysis - Tonetto, Mateus Rodrigues; Pinto, Shelon Cristina Souza; Rastelli, Alessandra de Nara Souza; Borges, Alvaro Henrique; Saad, José Roberto Cury [UNESP]; Pedro, Fábio Luis Miranda; Andrade, Marcelo Ferrarezi de [UNESP]; Bandéca, Matheus Coelho (Jaypee Brothers Medical Publishing, 2013)
Aims and objectives: The behavior of polymer-matrix composite is dependent on the degree of conversion. The aim of this study was to evaluate the degree of conversion of two resin cements following storage at 37°C immediately, 24 and 48 hours, and 7 days after light-curing by FTIR analysis. Materials and methods: The specimens were made in a metallic mold and cured with blue LED with power density of 500 mW/cm2 for 30 seconds. The specimens were pulverized, pressed with KBr and analyzed with FTIR following storage times. Statistical analysis used: ANOVA (two-way) and Tukey's post hoc. Results: To the polymer-matrix composites between 24 and 48 hours does not show a significant increase (p > 0.05), however, the highest values were found after 7 days. Conclusion: The polymer-matrix composites used in this study showed similarity on the degree of conversion and increased of according to the time of storage.
Keywords: Degree of conversion; FTIR analysis; Polymers; 2 hydroxyethyl methacrylate; 4 methacryloxyethyltrimellitic acid; 4-methacryloxyethyltrimellitic acid; bisphenol A bis(2 hydroxypropyl) ether dimethacrylate; carbon; macrogol derivative; methacrylic acid derivative; polymer; polymethacrylic acid derivative; polyurethan; resin; resin cement; tricarboxylic acid; triethylene glycol dimethacrylate; urethane dimethacrylate luting resin; chemistry; classification; dental bonding; dental curing light; human; infrared spectroscopy; materials testing; polymerization; radiation dose; radiation exposure; temperature; tight junction; time; Bisphenol A-Glycidyl Methacrylate; Carbon; Composite Resins; Curing Lights, Dental; Humans; Light-Curing of Dental Adhesives; Materials Testing; Methacrylates; Polyethylene Glycols; Polymerization; Polymethacrylic Acids; Polyurethanes; Radiation Dosage; Resin Cements; Self-Curing of Dental Resins; Spectroscopy, Fourier Transform Infrared; Temperature; Time Factors; Tricarboxylic Acids